2011
DOI: 10.1525/mp.2011.29.2.173
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Background Music on Cognitive Performance in Musicians and Nonmusicians

Abstract: there is debate about the extent of overlap between music and language processing in the brain and whether these processes are functionally independent in expert musicians. A language comprehension task and a visuospatial search task were administered to 36 expert musicians and 36 matched nonmusicians in conditions of silence and piano music played correctly and incorrectly. Musicians performed more poorly on the language comprehension task in the presence of background music compared to silence, but there was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 84 publications
(57 reference statements)
1
39
0
Order By: Relevance
“…This has many benefits, including enhanced auditory attention (Strait and Kraus, 2011a;Strait and Kraus, 2011b;, better processing of the metric structure of words when they are presented in sentences (Marie et al, 2011b) and the discrimination and identification of moraic language features (units of timing) (Sadakata and Sekiyama, 2011). Musicians can classify speech sounds (vowels) more easily and quickly than non-musicians (Bidelman et al, 2014), have advantages in relation to the processing of linguistic syntax (Fiveash and Pammer, 2014) and in making judgements about grammar (Patston and Tippett, 2011). They are better able to distinguish rapidly changing sounds (Gaab et al, 2005), harmonic differences (Corrigall and Trainor, 2009;Musacchia et al, 2008;Zendel and Alain, 2009) and tonal variations in non-native speech sounds (Chandrasekaran et al, 2009;Cooper and Wang, 2010;Kühnis et al, 2013;Marie et al, 2011a;Marie et al, 2011b;Marques et al, 2007;Martínez-Montes et al, 2013;Perfors and Ong, 2012;Slevc and Miyake, 2006;Wong and Perrachione, 2007;Yang et al, 2014).…”
Section: Research Comparing Musicians With Non-musiciansmentioning
confidence: 99%
“…This has many benefits, including enhanced auditory attention (Strait and Kraus, 2011a;Strait and Kraus, 2011b;, better processing of the metric structure of words when they are presented in sentences (Marie et al, 2011b) and the discrimination and identification of moraic language features (units of timing) (Sadakata and Sekiyama, 2011). Musicians can classify speech sounds (vowels) more easily and quickly than non-musicians (Bidelman et al, 2014), have advantages in relation to the processing of linguistic syntax (Fiveash and Pammer, 2014) and in making judgements about grammar (Patston and Tippett, 2011). They are better able to distinguish rapidly changing sounds (Gaab et al, 2005), harmonic differences (Corrigall and Trainor, 2009;Musacchia et al, 2008;Zendel and Alain, 2009) and tonal variations in non-native speech sounds (Chandrasekaran et al, 2009;Cooper and Wang, 2010;Kühnis et al, 2013;Marie et al, 2011a;Marie et al, 2011b;Marques et al, 2007;Martínez-Montes et al, 2013;Perfors and Ong, 2012;Slevc and Miyake, 2006;Wong and Perrachione, 2007;Yang et al, 2014).…”
Section: Research Comparing Musicians With Non-musiciansmentioning
confidence: 99%
“…Given the high levels of performance anxiety and perfectionism in music education (Osborne and Kenny 2005 ; Patston 2010 , 2014 ), a positive approach to problem solving will be helpful. Kirschenbaum et al ( 1982 ) suggested that there are two mechanisms that may lead positive reflection to work: (1) attention and (2) reinforcement.…”
Section: The Pims Modelmentioning
confidence: 99%
“…Basically, performing music was an activity that could train complex motor and cognitive functions, which couldn't be done by other cognitive activities. 22 When someone performed music, his/her nervous system was demanded to do certain tasks which wouldn't have been needed in other activities, e.g. controlling the rhythm and specific pitch.…”
Section: Discussionmentioning
confidence: 99%
“…24 In general, a musically active person would start doing the musical activities at the early stage of his/her life, when brain plasticity was at its peak. 22 Furthermore, according to Monaghan et al in Hanna-Pladdy & MacKay and Zatorre & McGill musical activities like playing musical instruments, creating music, and listening to music were able to stimulate several cognitive functions and were useful information for training induced brain plasticity which might happen at later age as a compensation for cognitive decrease related to age. 14,23 Similar statement was also expressed by Stern in Geda et al which stated that participation in cognitive activities, including playing musical instruments was most likely to encourage and stimulate the formation of neural networks in the brain that could inhibit the onset of dementia and Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation